Teacher’s Role and the Principles of Teaching Speaking Skill - Zainol Kamal (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2019)
Speaking is productively skill because it can create many words continuously go on. some students want to speak in a certain condition or stimuli. An event when the students express freely what the are feeling in front of the class without being shy to his/her friends. Of course it is not far from teacher’ role, how the teacher make his/her students become active in the class.So that’s why teacher role in this case is ultimate to create an active and creative students. Something that makes the role of teachet is important is if a teacher takes and play his/her role well applied un the class, it will indirectly motivate the students to show their ability up in front of the class and it will affect when the students are in public society. The research showed that teacher role is ultimate in education due to make a class comfort either for the students or for the teacher to reach educational purposes. Additionally, The teacher played the role in the class more namely as Learning Manager role that applied in the class. The reasons are to make students fell comfort in joining the class, to make the students build their confidence up in order to be able to speak English, etc. Based on the result above, it is suggested for the English teacher to select the approppriate roles needed by the students. Teacher may combine or use more than one role in one subject. Then, teacher should pay attention to the students development in terms of students’ speaking ability and have something which challege or treats the students more to speak such as using game or role play. Key Word : Teacher’s Role, Principles of teaching and Speaking